#### Answer

$y' = -cosecx\ cotx -\frac{2}{\sqrt x} -\frac{7}{e^{x}}$

#### Work Step by Step

$y = cosecx -4\sqrt x + \frac{7}{e^{x}}$
$y' = -cosecx\ cotx -\frac{2}{\sqrt x} -\frac{7}{e^{x}}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = -cosecx\ cotx -\frac{2}{\sqrt x} -\frac{7}{e^{x}}$

$y = cosecx -4\sqrt x + \frac{7}{e^{x}}$
$y' = -cosecx\ cotx -\frac{2}{\sqrt x} -\frac{7}{e^{x}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.